A COMPARATIVE PERSPECTIVE TO MIDDLE EAST-TURKEY RELATIONS: IRAN IRAQ AND SYRIA AXIT (1979-2003) - DİYARBAKIRLIOĞLU , Kaan (SSD Journal, 2021)
Turkey-Middle East relations vary in parallel with the changes that occur in each period. As a leader in the dependent variable and changes occurring in the international system, regardless of Turkey's relations constitute the main axis of shaping the Middle East. In 1980, Turkey's domestic politics in the main square of this article is to try to analyze the policies implemented starting from the change from a maximum of crises in Turkey's foreign policy experience in Iraq, it is Iran and Syria as the focal point. At the same time the changes occurring in these countries themselves, periods are shaping the policies implemented by Turkey. Therefore attitude demonstrated in Turkey's problems in these countries will be examined by an analytical perspective. Finally, in this study, the substructure and the differences between the policies formed by giving place to the statements and statements of the leaders were analyzed.